1973
DOI: 10.1007/bf00357646
|View full text |Cite
|
Sign up to set email alerts
|

The puromycin reaction mediated by yeast ribosomes in high salt

Abstract: The extend of the reaction between puromycin and yeast peptidyl-tRNA prelabeled in vitro was determined by measuring the distribution of trichloroacetic acid precipitable material in isokinetic sucrose gradients in the presence of 0.5 M KCl.Thus it was found that increasing amounts of puromycin remove increasing amounts of peptidyl-tRNA from the 80S position in the gradient. The extend of the reaction, however, was independent of pretreatment of the ribosomes with inhibitors of the translocation indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Next, various salt mix concentrations were tested during post translation incubation. Previously, a high concentration of KCl has been shown to improve the accessibility of ribosomebound peptidyl-tRNA to puromycin (Van Der Mast & Bloemers, 1973) and has been adopted in the recent mRNA and cDNA display methods (Naimuddin & Kubo, 2016;Seelig, 2011;Yamaguchi et al, 2009). We found that without salt addition, conjugate formation is less than 10%, however the addition of 32.5 mM MgCl 2 and 375 mM KCl greatly increased the formation rate to above 40% ( Figure 2B).…”
Section: Optimization Of Conjugate Formation During In Vitrotranslationmentioning
confidence: 69%
“…Next, various salt mix concentrations were tested during post translation incubation. Previously, a high concentration of KCl has been shown to improve the accessibility of ribosomebound peptidyl-tRNA to puromycin (Van Der Mast & Bloemers, 1973) and has been adopted in the recent mRNA and cDNA display methods (Naimuddin & Kubo, 2016;Seelig, 2011;Yamaguchi et al, 2009). We found that without salt addition, conjugate formation is less than 10%, however the addition of 32.5 mM MgCl 2 and 375 mM KCl greatly increased the formation rate to above 40% ( Figure 2B).…”
Section: Optimization Of Conjugate Formation During In Vitrotranslationmentioning
confidence: 69%
“…Translation time reflects the ribosome loading and translation of the coding region which ends up stalling at the 3' end due to lack of stop codon. Previously, a high concentration of KCl has been shown to improve the accessibility of ribosome‐bound peptidyl‐tRNA to puromycin (Van Der Mast & Bloemers, 1973) and has been adopted in the recent mRNA and cDNA display methods (Naimuddin & Kubo, 2016; Seelig, 2011; Yamaguchi et al, 2009). Hence, we tested various salt concentration and found that without salt addition, conjugate formation is less than 10%, however, the addition of 375 mM KCl and 32.5 mM MgCl 2 greatly increased the formation rate to above 40% (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%